2022
DOI: 10.1080/15548627.2022.2062888
|View full text |Cite
|
Sign up to set email alerts
|

Starvation after infection restricts enterovirus D68 replication

Abstract: Enterovirus D68 (EV-D68) is a respiratory pathogen associated with acute flaccid myelitis, a childhood paralysis disease. No approved vaccine or antiviral treatment exists against EV-D68. Infection with this virus induces the formation of autophagosomes to enhance its replication but blocks the downstream autophagosome- lysosome fusion steps. Here, we examined the impact of autophagy induction through starvation, either before (starvation before infection, SBI) or after (starvation after infection, SAI) EV-D68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…TFEB cleavage during enteroviral infection could be significant for many reasons. First, even though EV-D68 and other enteroviruses are known to use components of autophagic signaling for their benefit, we have recently shown that stress-induced autophagy via amino acid starvation during infection (starvation after infection) impairs the infection of multiple enteroviruses, including EV-D68, CVB3, Rhinovirus-14, and Poliovirus (6). Recent unpublished data from our lab shows that TFEB regulates this stress-induced antiviral autophagy (Jassey et al manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFEB cleavage during enteroviral infection could be significant for many reasons. First, even though EV-D68 and other enteroviruses are known to use components of autophagic signaling for their benefit, we have recently shown that stress-induced autophagy via amino acid starvation during infection (starvation after infection) impairs the infection of multiple enteroviruses, including EV-D68, CVB3, Rhinovirus-14, and Poliovirus (6). Recent unpublished data from our lab shows that TFEB regulates this stress-induced antiviral autophagy (Jassey et al manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…EV-D68 belongs to the Piconarviridae family of positive sense single-strand RNA viruses, with a genome size of about 7500 nucleotides, encoding a single polyprotein post-translationally processed to structural and nonstructural proteins (4). Like other enteroviruses, infection with EV-D68 leads to an extensive reconfiguration of cellular membranes, and double-membrane autophagosome-like vesicles, which support various phases of the viral life cycle, including genomic RNA replication and nonlytic release, can be observed late during EV-D68 infection (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…This finding also recapitulates earlier studies showing that the Fermon strain does not infect neuronal cell lines (SH-SY5Y) or cause paralysis in mice ( 12 , 14 ) but differs from another study that demonstrated that Fermon infects human iPSC-derived cortical neuron and astrocyte cultures ( 16 ). It is unknown whether these differences are attributable to differences in cell type and receptor expression, viral multiplicity of infection (MOI), or availability of exosomes, as recent studies have suggested that EV-D68 may use exosomal association as a receptor-independent cell-entry mechanism ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human spinal cord tissue is infrequently available for study, as patients rarely expire during their acute illness, and the spinal cord cannot be safely biopsied. Prior human CNS models for EV-D68 infection include neuronal cell lines and induced pluripotent stem cell (iPSC)-derived neurons or astrocytes ( 14 - 18 ) as well as brain organoids ( 19 ). However, EV-D68 is not a pathogen that commonly causes encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although EV-D68 is known to induce autophagy and block the downstream autophagic maturation, how exactly EV-D68 infection causes autophagy and the specific viral protein(s) involved is not entirely understood (30, 31). Our finding that EV-D68 infection induces SIRT-1 translocation starting at 3 hpi, which coincides with the emergence of lipidated LC3, suggests that SIRT-1 may be essential for virus-induced changes in the autophagic pathway.…”
Section: Discussionmentioning
confidence: 99%